Multicenter Observational Study of the Development of Progressive Organ Dysfunction and Therapeutic Interventions in Normotensive Sepsis Patients in the Emergency Department. (14th May 2013) - Arnold, Ryan C.; Sherwin, Robert; Shapiro, Nathan I.; O'Connor, Jennifer L.; Glaspey, Lindsey; Singh, Sam; Medado, Patrick; Trzeciak, Stephen; Jones, Alan E.; ,; Merchant, Roland C.
Abstract Objectives Progressive organ dysfunction is the leading cause of sepsis‐associated mortality; however, its incidence and management are incompletely understood. Sepsis patients with moderately impaired perfusion (serum lactate 2.0 to 3.9 mmol/L) who are not in hemodynamic shock ("preshock" sepsis patients) may be at increased risk for progressive organ dysfunction and increased mortality. The objectives of this study were to: 1) quantify the occurrence of progressive organ dysfunction among preshock sepsis patients, 2) examine if there were baseline differences in demographic and physiologic parameters between preshock sepsis patients who experienced progressive organ dysfunction and those who did not, and 3) examine if intravenous (IV) fluid administered in the emergency department (ED) differed between these two groups of patients. Methods This was a prospective, observational study in four urban EDs targeting the preshock sepsis population, defined as adults (18 years or older) with suspected infection, serum lactate between 2.0 and 3.9 mmol/L, and without hypotension (systolic blood pressure [sBP] < 90 mm Hg or mean arterial pressure [MAP] < 70 mm Hg) or requiring mechanical ventilation at ED presentation. The primary composite outcome was progressive organ dysfunction, defined as a rise in the Sequential Organ Failure Assessment (SOFA) score of ≥1, vasopressor use, mechanical ventilation use within 72 hours after ED presentation, or in‐hospital death. The secondary outcomes were any intensive care unit (ICU) admission, and total ICU and hospital lengths of stay (LOS). Results Among 94 preshock sepsis patients, the primary composite outcome occurred in 24 of 94 (26%). In patients with the primary outcome, 22 of 24 (92%) experienced a rise in SOFA score of ≥1, five of 24 (21%) received vasopressor agents, and seven of 24 (30%) required mechanical ventilation. There were no baseline demographic or physiologic parameter differences between patients who met the primary outcome versus those who did not, while patients with the primary outcome had a higher average SOFA score at admission (2.4 vs. 1.3, p = 0.011) and at all subsequent time points. Median IV fluid volume administered to all preshock sepsis patients during their ED stay was 1, 225 mL (interquartile range [IQR] = 712 to 2, 000 mL) and did not differ significantly between patients with (1, 150 mL, IQR = 469 to 2, 000 mL) or without (1, 250 mL, IQR = 750 to 2, 000 mL) the primary outcome (p = 0.73). Patients with progressive organ dysfunction or death were more likely to be admitted to an ICU (50% vs. 20%, p < 0.01) and have an increased median hospital LOS (6 days vs. 3 days, p = 0.005), compared to those without progressive organ dysfunction. Conclusions Over one‐quarter of preshock sepsis patients developed progressive organ dysfunction with associated increased resource use. Demographic and physiologic parameters were unable to differentiate patients with progressive organ dysfunction, while the initial SOFA score was increased in patients meeting the outcome. Overall, these patients received relatively little IV fluid therapy during their ED stays. Further research to determine if more aggressive therapy can prevent progressive organ dysfunction in this population is warranted.